2008
DOI: 10.1002/jor.20692
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin improves functional and histological recovery of traumatized skeletal muscle tissue

Abstract: Apart from its hematopoietic effect, erythropoietin (EPO) is known as pleiotropic cytokine with anti-inflammatory and antiapoptotic properties. Here, we evaluated for the first time the EPO-dependent regeneration capacity in an in vivo rat model of skeletal muscle trauma. A myoblast cell line was used to study the effect of EPO on serum deprivation-induced cell apoptosis in vitro. A crush injury was performed to the left soleus muscle in 80 rats treated with either EPO or saline. Muscle recovery was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 44 publications
1
74
1
Order By: Relevance
“…Several studies have attested EPO anti-apoptotic properties in traumatic, ischemic and toxic injury in a multitude of organs, such as the skeletal muscle, 35 liver 36 and kidney. 11 Our results showed that administration of EPO significantly decreased the number of apoptotic cells when compared with untreated flaps and animals receiving L-Name only.…”
Section: Epo Enos Ischemic Damage and Skin F Rezaeian Et Almentioning
confidence: 99%
“…Several studies have attested EPO anti-apoptotic properties in traumatic, ischemic and toxic injury in a multitude of organs, such as the skeletal muscle, 35 liver 36 and kidney. 11 Our results showed that administration of EPO significantly decreased the number of apoptotic cells when compared with untreated flaps and animals receiving L-Name only.…”
Section: Epo Enos Ischemic Damage and Skin F Rezaeian Et Almentioning
confidence: 99%
“…HSP, a stress protein, is synthesized shortly after cells are exposed to stress or a rapid rise in temperature 14) . It functions to minimize cell injury by maintaining proper protein folding with degenerative enzyme proteins and by supporting intracellular homeostasis, including protein transport and synthesis 4,15) . Although HSP 70 is spontaneously expressed under rapidonset pathological conditions, it does not sufficiently protect against cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, muscle healing involves the formation of connective scar tissue, not primarily regeneration. The healing process of injured muscle can frequently be hampered by the formation of scar tissue which is characterized by extensive muscle fibrosis and can lead to recurrence of muscle injury 4) . Thus, a therapeutic approach in this phase is important to decrease scar tissue and promote the alignment of muscle fiber for normal contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, following extensive cardiotoxin-induced muscle damage (38-67% of muscle fibers 8 ), regeneration is mediated by satellite cells, the resident stem cells that mature to ultimately become functional muscle fibers 4,[9][10][11][12][13] . The end result is increased post-damage functional regeneration of healthy, force-producing muscle tissue [14][15][16] . Although the details are well beyond the scope of this report, the mechanistic basis for muscle regeneration reflects the carefully orchestrated events of numerous cell types from multiple lineages utilizing canonical signaling pathways critical to both tissue development and morphogenesis 5,[17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%